Programming the integration of robot motion and vision for an industrial robot / Mohamad Farizal Rajemi - Rajemi, Mohamad Farizal (2004)
The paper reports on work recently carried out to integrate the ASEA IRE 6 industrial robot motion with camera Baxall CD9752 vision system. The development of the software includes the synchronization of the robot arm, detection of an object on test table and the operation of the robot arm to pick up the object on the test table. In evaluating the experiment, 7 random points are being selected in the active camera area to determine the difference between Ole actual location of the end effector and the calculated calculation using two methods i.e. Ole trigonometric solutions and the Denavit Hartenberg (DH) parameters. In so doing, both the concepts of forward and inverse kinematics are demonstrated.